Carbon dioxide sequestration process for the cement industry. (December 2019) - Youn, Min Hye; Park, Ki Tae; Lee, Ye Hwan; Kang, Seong-Pil; Lee, Sang Moon; Kim, Sung Su; Kim, Young Eun; Ko, You Na; Jeong, Soon Kwan; Lee, Wonhee
Graphical abstract: Highlights: KCl and CaCl2 were extracted using pure water and HCl solutions at various concentrations, respectively, from industrial cement kiln dust. For the membrane electrolysis, higher anolyte/lower catholyte concentrations, and higher temperature are appropriate for KOH production. The CO2 capture-mineralization was tested by measurement of CO2 removal efficiency depending on the Ca/CO2 ratio and gas retention time. Abstract: Due to the significant amount of CO2 released from the cement industry, a CO2 sequestration process suitable for cement-manufacturing plants is required to reduce greenhouse gas emission and to mitigate global warming. In the present study, a new overall process of CO2 treatment is proposed for the cement industry that includes the extraction of KCl and CaCl2 from the cement by-products, KCl membrane electrolysis for KOH formation, and CO2 capture-mineralization using the extracted KOH and CaCl2 . For this three-step process, various experiments were conducted to determine how the results varied in relation to experimental conditions and to find the most suitable conditions for process operation. The KCl and CaCl2 were extracted using pure water and HCl solutions at various concentrations, respectively, from industrial cement kiln dust. KCl membrane electrolysis was carried out to measure the electrochemical performance in relation to the KCl or KOH concentration, temperature, and applied current density. The single process of CO2 capture-mineralization was tested by measurement of the CO2 removal efficiency in relation to variation of the Ca/CO2 ratio and gas retention time. In addition, the purity of the CaCO3 produced was evaluated in relation to the Ca/CO2 ratio, and the CO2 removal efficiency was examined over time on stream.